The Scholar as Squirrel: Everyday Collecting in Academia - Löfgren, Orvar (Hamburger Journal für Kulturanthropologie (HJK), 2015)
This paper looks at collecting practices in the everyday world of universities. How do scholars turn into hoarding squirrels, creating their own archives? My focus is on routines and technologies, which deal with storage and order as well as retrieving and discarding of research materials.